The Idea of Renewing Terrorism Criminal Law in Indonesia as an Effort to Overcome Terrorism Based on the Justice Values - Zarzani, Tengku Riza; Fitrianto, Bambang; Annisa, Siti (UNISSULA, 2024)
This study aims to reconstructs the Constitution Act on Criminal Terrorism in Indonesia, with the objective of strengthening the framework law to cope with terrorism while ensuring protection, mark justice, and basic human rights. The purpose of this research to analyze about Terrorism Crime, Constitution Act Criminal Terrorism that occurs in Indonesia at the moment This Not yet can fulfill a sense of justice and Reconstruction Constitution Act Criminal Terrorism as effort countermeasures terrorism in Indonesia based mark justice. With a juridical, normative, and qualitative data analysis approach and analyze legal norms and principles relevant to justice with regard to criminal terrorism. The main problem found covers the following definitions: criminal extensive terrorism, potential abuse authority in detention and wiretapping, as well as the need for enhancement efforts to prevent terrorism. Research results show the necessity of a revision of the law to clarify the definition of criminal terrorism, limit detention and wiretapping with tight supervision, and also focus more on prevention through education and deradicalization. Proposed recommendations include strengthening cooperation between the government, institutions, security, and civil society, as well as integrating deradicalization and education programs to prevent the spread of ideological terrorism.